PSIKOEDUKASI KESEHATAN MENTAL PADA SISWA KELAS X SMA BATIK 1 SURAKARTA - Nugroho, Novan; Purnomosidi, Faqih (Jurnal Edukasi Pengabdian Masyarakat, 2025)
In recent years, the increasing cases of mental health disorders among adolescents, especially high school students, have become an increasingly emerging issue. Given that adolescence is a crucial stage of development that is very vulnerable to psychological problems, intervention through psychoeducation is important. Psychoeducation aims not only to provide an understanding of mental health, but also to encourage students to care more about their own and others' psychological conditions. This study is important to determine the extent to which psychoeducation is effective in increasing students' collective awareness to maintain each other's mental health, especially in the school environment. Psychoeducational activities were carried out in the form of a survey filling out a google form about how important mental health is for students and delivering material entitled "Mental Health: It's Okay To Not Be Okay" to students in grades X.13, X.1 and X.10 at SMA Batik 1 Surakarta. The results of this activity showed a transformation in participants' attitudes, which was marked by students validating their mental condition from the material presented, there were also students who cried and the willingness of students to maintain each other's mental health together.